Critical Review of Technology, Simulation Training, and Decision-Making in Emergency Medicine - Alanazi, Ahmed Dhaher; Aldhafeeri, Mohammed Mubarak; Alshammari, Meshal Zayed Mashaan; Alnasafi, Saad Alhumaidi Saad; Almutairi, Fahad Mohammed; Alharbi, Fahad Saad; Alshammary, Saud Batty; Alanazi, Ahmed Abdullah Ruhail (Journal of Ecohumanism, 2024)
Flourishing demand associated with the speed and precision of clinical decisions that are required in the field of emergency medicine has influenced the use of new-generation simulation technologies. Multiple benefits of simulation training include the creation of a realistic clinical learning environment, improved healthcare professionals’ cognitive skills, effective teamwork, and overall preparedness. This paper presents a systematic critique of the use of technology in the evidence-based practice of simulation education and its effects on decision-making in emergency medicine. The paper consolidates current evidence, incorporates relatively new developments like VR, AR, and high-fidelity mannequins, and discusses issues related to cost, accessibility, and feasibility. Research evidence shows that it is effective in clinical decision-making improvement and patient results, but there are inequalities in its application.